Examining the Economic Impact of Renewable Energy in Green Buildings: A Case Study of Jordan - Albaali, Ghani; Shahateet, Mohammed; AL-Naif, Khaled; Altayeb, Saud; Saidi, Abdul Ghafoor (International Journal of Energy Economics and Policy, 2020)
This paper aims at testing whether an increase in energy spending has placed a negative or positive impact on the Jordanian economy. Following the economic scale theory and the results of model simulation, we reached to a conclusion that such level of growth in public spending threatens the next generations living in Jordan, as the gap between produced energy and the total energy used. The question is how to shrink this energy gap, or even eliminate it. The paper contributes to bridging such gap by suggesting an increase in the production of domestic energy which depends on what resources Jordan has and whether these resources are renewable or fossil as well as the economic feasibility of using such resources. The influential use is related to social awareness as well as to the supports that are given by government regulations. The paper concludes that it is about time to reduce the amount of support needed by residential energy users in order to invest in other energy projects such as hydroelectric, wind, or large solar farms. Keywords: Renewable energy, green building, energy spending, Jordan JEL Ð¡lassifications: O13, Q43, Q48, Q51, Q56 DOI: https://doi.org/10.32479/ijeep.9947